The role of provincial health administration in supporting district health management teams in the Democratic Republic of Congo: eliciting an initial programme theory of a realist evaluation - Samuel Bosongo; Zakaria Belrhiti; Faustin Chenge; Bart Criel; Yves Coppieters; Bruno Marchal (BMC, 2024)
Abstract Background In 2006, the Ministry of Health in the Democratic Republic of Congo designed a strategy to strengthen the health system by developing health districts. This strategy included a reform of the provincial health administration to provide effective technical support to district health management teams in terms of leadership and management. The provincial health teams were set up in 2014, but few studies have been done on how, for whom, and under what circumstances their support to the districts works. We report on the development of an initial programme theory that is the first step of a realist evaluation seeking to address this knowledge gap. Methods To inform the initial programme theory, we collected data through a scoping review of primary studies on leadership or management capacity building of district health managers in sub-Saharan Africa, a review of policy documents and interviews with the programme designers. We then conducted a two-step data analysis: first, identification of intervention features, context, actors, mechanisms and outcomes through thematic content analysis, and second, formulation of intervention-context-actor-mechanism-outcome (ICAMO) configurations using a retroductive approach. Results We identified six ICAMO configurations explaining how effective technical support (i.e. personalised, problem-solving centred and reflection-stimulating) may improve the competencies of the members of district health management teams by activating a series of mechanisms (including positive perceived relevance of the support, positive perceived credibility of provincial health administration staff, trust in provincial health administration staff, psychological safety, reflexivity, self-efficacy and perceived autonomy) under specific contextual conditions (including enabling learning environment, integration of vertical programmes, competent public health administration staff, optimal decision space, supportive work conditions, availability of resources and absence of negative political influences). Conclusions We identified initial ICAMO configurations that explain how provincial health administration technical support for district health management teams is expected to work, for whom and under what conditions. These ICAMO configurations will be tested in subsequent empirical studies.